The Effectiveness of Hybrid Learning on RPL (Recognition of Prior Learning) Students at Panca Marga University - Linda Kurnia Supraptiningsih; Faridahtul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the effectiveness of hybrid learning for RPL (Recognition of Prior Learning) students at Panca Marga University. Hybrid learning, which combines face-to-face and online instruction, addresses scheduling challenges faced by working students. Using a quantitative approach and survey methods, the study evaluates the impact of hybrid learning on learning flexibility, engagement, and academic outcomes. Results show that hybrid learning enhances flexibility, allows students to balance work and study, and improves learning outcomes by 15% compared to conventional methods. However, challenges such as internet dependence and digital fatigue remain significant. The study highlights the need for technological infrastructure and faculty training to optimize hybrid learning implementation.